2013
DOI: 10.5455/2320-1770.ijrcog20130929
|View full text |Cite
|
Sign up to set email alerts
|

Non closure of parietal peritoneum at cesarean section and adhesion formation

Abstract: Background: Cesarean section is the most commonly performed surgery worldwide. Recent times have seen rising trends in c-section rates, for a variety of reasons. Although the basic procedure remains same, some new techniques have been adopted like not closing the visceral or the parietal peritoneum. A large number of studies on merits and demerits of these practices have been published, generating even larger debates. Objective of this effort is to evaluate studies on either side of the argument and cite our e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In contrast to this result, Rafique et al (6) did not show any significant difference regarding length of post-operative hospital stay between the closure and non-closure groups. On the other hand, Choudhary et al (12) showed decreased postoperative hospital stay in the closure group because it depends on the technique of the previous CS, which was not included in our study.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In contrast to this result, Rafique et al (6) did not show any significant difference regarding length of post-operative hospital stay between the closure and non-closure groups. On the other hand, Choudhary et al (12) showed decreased postoperative hospital stay in the closure group because it depends on the technique of the previous CS, which was not included in our study.…”
Section: Discussionmentioning
confidence: 70%
“…On the other hand there was no statistically significant difference regarding the pain degree and the analgesia requirements. In the study by Choudhary et al (12) the non-closure group had more postoperative pain because of the presence of adhesions due to nonclosure of peritoneum during primary CS, our study was deficient in the history of previous CS technique.…”
Section: Discussionmentioning
confidence: 78%
“…They observed more blood loss and postoperative periods were turbulent with longer hospital stays in these patients. 11 Lyell et al found that parietal peritoneal closure at primary caesarean delivery was 5fold protective against all adhesions and 3-fold protective against dense adhesions. 12 Thereby confirming long term better outcome in CG.…”
Section: Discussionmentioning
confidence: 99%
“…A 2% lignocaine hydrochloride (Netagi, Mumbai, India) was administered at 10 mg/kg subcutaneously in inverted "L" technique; 3 cm caudal and dorsal to the initial left-oblique-laparotomy, where incision was made for the gross examination of the initial laparotomy incision sites, for tissue adhesions and other post-operative complications. The adhesion was scored grade 0, 1, 2 and 3 as none, mild, moderate and severe adhesion respectively (Table I) based on the severity and percentage of goats involved according to Choudhary and Bansal (2013). The omentopexy was removed, the laparotomy closed in standard procedure (Kersjes et al,.…”
Section: Clinical Assessmentmentioning
confidence: 99%